2020
DOI: 10.1038/s41598-020-72636-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cold plasma processing on major peanut allergens

Abstract: Cold plasma is emerging as a novel food processing technology, with demonstrated efficacies for microbial inactivation and residual chemical dissipation of food products. Given the technology’s multimodal action it has the potential to reduce allergens in foods, however data on the efficacy and mechanisms of action are sparse. This study investigates the efficacy of cold plasma on major peanut allergens (Ara h 1 and Ara h 2). For this purpose, dry, whole peanut (WP) and defatted peanut flour (DPF) were subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…The intensity of HRP bands decreased in a time-dependent manner after DBD plasma treatment (Figure 4A). These data are consistent with previous findings (Ng et al, 2020;Venkataratnam et al, 2020). For instance, SDS-PAGE analysis indicated that the band intensity of casein declined dramatically with an increasing treatment time of spark discharge and glow discharge plasma (Ng et al, 2020).…”
Section: Inactivation Of Hrp Induced By Dbd Plasmasupporting
confidence: 92%
See 1 more Smart Citation
“…The intensity of HRP bands decreased in a time-dependent manner after DBD plasma treatment (Figure 4A). These data are consistent with previous findings (Ng et al, 2020;Venkataratnam et al, 2020). For instance, SDS-PAGE analysis indicated that the band intensity of casein declined dramatically with an increasing treatment time of spark discharge and glow discharge plasma (Ng et al, 2020).…”
Section: Inactivation Of Hrp Induced By Dbd Plasmasupporting
confidence: 92%
“…For instance, SDS-PAGE analysis indicated that the band intensity of casein declined dramatically with an increasing treatment time of spark discharge and glow discharge plasma (Ng et al, 2020). Similar findings were also reported by Venkataratnam et al (2020), who found that cold plasma caused degradation of Ara h1 and Ara h2 with SDS-PAGE, two major peanut allergens. The decrease in band intensity following DBD plasma treatment may be due to the oxidative damage of HRP.…”
Section: Inactivation Of Hrp Induced By Dbd Plasmasupporting
confidence: 81%
“…Many studies have utilized CAP for the decontamination of (bio)chemical contaminants, such as mycotoxins from fungi (Wielogorska et al., 2019; Hojnik, Modic, Tavčar‐Kalcher et al., 2019; Hojnik et al., 2017), prions (Elmoualij et al., 2012; Shintani, 2012; Baxter et al., 2005), proteins and enzymes (Laroussi, 2018; Misra, Pankaj, Segat et al., 2016; Takai et al., 2014), allergens (Ng et al., 2021; Venkataratnam et al., 2020; Venkataratnam et al., 2019; Ekezie et al., 2018; Meinlschmidt et al., 2016), and pesticides (Toyokawa et al., 2018; Misra, Pankaj et al., 2014).…”
Section: Industry Implementation and Applicationsmentioning
confidence: 99%
“…This is consistent with prior reports in the literature that have demonstrated that a peanut allergen reaction is often the most severe, and is the leading cause of deadly anaphylaxis. 36 Additionally, egg, soybean and milk allergies were relatively mild compared to peanut allergy. AllerCatPro (https://allercatpro.bii.a-star.edu.sg/ ) was used to predict the potential allergenicity of the proteins and it was found that allergenicity was associated with the epitopes (these data are provided in the ESI †).…”
Section: Papermentioning
confidence: 99%